Misconception tendency of differentiated instruction in publicly shared teaching and learning videos on youtube: A mixed-methods exploration study - Putra, Guruh Sukarno (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2023)
Differentiated instruction is a pedagogical approach in which teachers fulfill students' needs based on their interests and learning profiles. This paradigm is new to the Indonesian educational sector as the government of Indonesia introduced the Merdeka curriculum in 2022, which offers a new style of teaching and learning in Indonesia through differentiation in the classroom. As an unfamiliar approach, the recent practice of differentiated instruction may lead to a misconception, particularly in its implementation. This paper focuses on witnessing teachers' misconceptions regarding differentiated instruction in three major aspects: teacher-student relations, teacher-learning design, and teacher-learning goals, using a mixed method with an explanatory sequential design. The first phase includes video observation for qualitative data collection to build variables and obtain quantitative results. This research used a purposive sampling technique with a total of seventy-seven teaching and learning in Indonesian high school videos from YouTube with particular keywords related to differentiation. All the videos were uploaded on YouTube in 2022, ranging from January 2022 to December 2022, and were from various origins and subjects. The final result and interpretation show that the score of differentiated instruction implementation through the observation checklist was 0.4722, considered satisfactory. Furthermore, this study identifies three aspects of differentiation that need to be strengthened, including learning pace settings, giving oral feedback to students based on their needs, and responding proactively to diverse students. The recommendations for tackling misconceptions regarding differentiated instruction are given for better future implementation.